Cationic Antimicrobial Peptides of Respiratory Tract Nonspecific Defense System: Defensins and Cathelicidins. Defensins - Molecules Undergoing a Renaissance (Part 4) - A.Ye. Abaturov (Zaslavsky O.Yu., 2012)
This review presents the main systemic actions of defensins. Special attention is paid to modulatory effects of defensins on the processes of inflammation and immune response.